Esaxerenone inhibits the macrophage-to-myofibroblast transition through mineralocorticoid receptor/TGF-β1 pathway in mice induced with aldosterone - Qiang, Panpan; Hao, Juan; Yang, Fan; Han, Yutong; Chang, Yi; Xian, Yunqian; Xiong, Yunzhao; Gao, Xiaomeng; Liang, Lijuan; Shimosawa, Tatsuo; Xu, Qingyou (Frontiers in Immunology, 2022)
Renal fibrosis is the inevitable pathway of the progression of chronic kidney disease to end-stage renal disease, which manifests as progressive glomerulosclerosis and renal interstitial fibrosis. In a previous study, we observed severe interstitial fibrosis in the contralateral kidneys of 6-month unilateral ureteral obstruction (UUO) rats, which was accompanied by increased macrophage infiltration and phenotypic transformation; after eplerenone administration, these effects were reduced. Therefore, we hypothesized that this effect was closely related to mineralocorticoid receptor (MR) activation induced by the increased aldosterone (ALD) level. In this study, we used uninephrectomy plus continuous aldosterone infusion in mice to observe whether aldosterone induced macrophage-to-myofibroblast transition (MMT) and renal fibrosis and investigated the signaling pathways. Notably, aldosterone induced predominantly M1 macrophage-to-myofibroblast transition by activating MR and upregulating TGF-β1 expression, which promoted renal fibrosis. These effects were antagonized by the MR blocker esaxerenone. These findings suggest that targeting the MR/TGF-β1 pathway may be an effective therapeutic strategy for renal fibrosis.